Implementation Challenges and Potential Evils of Uniform Civil Code in India: a Multidimensional Analysis - Aarif Mohd Waza (MultiTech Publisher, 2023)
This research paper examines the challenge and potential drawbacks associated with the implementation of uniform civil code in India. The concept of uniform civil code aims to establish common laws for all citizens, irrespective of their religious and traditional affiliations. However, given the diverse religious and cultural landscape of India the imposition of such a code raises concerns about religious autonomy and cultural preservation. The paper delves into the various conflicts that may arise from implementing a uniform civil code including opposition from religious groups, resistance to change and debates over gender justice. It also explorers the legal and implementation challenges involved emphasizing the need for a diplomatic and continuous approach that respects the sensitivities of different communities. Further more, this paper draws lessons from the experience of the countries that have implemented uniform civil code, highlighting the importance of social acceptance, sensitisation and preserving religious and cultural diversity. It suggests that alternative approaches such as reforming and harmonizing existing personal laws. Selectively implementing reforms, promoting community mediation, embracing legal pluralism or maintaining existing personal laws could address legal and societal issues while respecting India’s diversity. In conclusion the research paper emphasizes the significance of considering these challenges and alternatives in discussions surrounding the implementation of a uniform civil code in India.